2017
DOI: 10.1038/s41388-017-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Murine stroma adopts a human-like metabolic phenotype in the PDX model of colorectal cancer and liver metastases

Abstract: Cancer research is increasingly dependent of patient-derived xenograft model (PDX). However, a major point of concern regarding the PDX model remains the replacement of the human stroma with murine counterpart. In the present work we aimed at clarifying the significance of the human-to-murine stromal replacement for the fidelity of colorectal cancer (CRC) and liver metastasis (CRC-LM) PDX model. We have conducted a comparative metabolic analysis between 6 patient tumors and corresponding PDX across 4 generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…Recent work showed that PDX propagation causes changes in DNA copy number, allowing clones with a minor representation in the xenograft to obtain a fitness advantage over the course of PDX passage [6]. On the other hand, murine stroma cells adapt a human-like metabolome profile in PDXs [30]. Given the divergent and common features of PDX models and primary tumors, an extended PDX-tailored classifier that includes multiple molecular features should be developed and trained on the growing number of thoroughly characterized CRC PDX samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that PDX propagation causes changes in DNA copy number, allowing clones with a minor representation in the xenograft to obtain a fitness advantage over the course of PDX passage [6]. On the other hand, murine stroma cells adapt a human-like metabolome profile in PDXs [30]. Given the divergent and common features of PDX models and primary tumors, an extended PDX-tailored classifier that includes multiple molecular features should be developed and trained on the growing number of thoroughly characterized CRC PDX samples.…”
Section: Discussionmentioning
confidence: 99%
“…Second, human tumor stromal cells and extracellular matrix (ECM) that are transplanted into immunodeficient mice are likely replaced by mouse tissue, which can significantly impair studies of the tumor microenvironment (TME) and cancer immunotherapy in PDX models . To some extent, mouse stromal cells in the TME share common features with matched human cells in parental tumors, but the exact impact of murine stroma on human cancer cells in PDX models remains unknown. Third, the engraftment of a PDX can cause lymphoma but not the expected tumors in host mice if the donor patient has a history of Epstein Barr virus infection …”
Section: Introductionmentioning
confidence: 99%
“…As summarized above, in general UC PDX maintain the genetic background of their donor patient tumors and can also retain patient stromal cells at early passages. In addition, a recent report in colorectal cancer PDX models showed that after the early replacement of the human stroma by murine cells, the murine stroma adopts a human-like metabolic phenotype suggesting that the PDX stroma recapitulates primary tumor stroma in important ways [51]. If a similar adaptation take place in UC PDX, it will also be a great advantage for future translational studies aiming at assessing therapies and concepts that involve both cancer cells and stroma.…”
Section: Discussionmentioning
confidence: 99%